Injustiça estrutural e responsabilidade política compartilhada no pensamento de Iris Marion Young - Araujo, Rayanne Saturnino de (2019)
Iris Marion Young (1949-2006) researched topics such as gender, social oppression, democracy, justice, race, equality, globalization, and international relations. In this research, I propose to explore your reflections on the theme of justice, specifically, I want to understand how the concept of shared political responsibility, developed by her, becomes central to the reduction of structural injustices. To this end, I make a conceptual analysis of Young’s reflections on the themes of justice/injustice, recognition, democracy and political responsibility. In this process I analyze several concepts that Young elaborated to: make a critique of the distributive paradigm of justice; situate democracy as a means to promote justice; and devise a way to consider the unintentional actions of individuals on the theme of justice. I consider as research source her three main books: Justice and the Politics of Difference (1990), Inclusion and Democracy (2002), and Responsibility for Justice (2011) and other articles related to the topics covered. It was possible to identify that Young’s thought has many contributions to the theme of justice, but there are also some underdeveloped aspects. Young understands that justice must be grounded in Habermas’s ethics of communicative action, not in the notion of social contract as Rawls does. She suggests that we should broaden the scope of justice beyond distributive issues to consider other types of relationships that also give rise to injustices, such as division of labor, decision-making processes, and culture. Young is more concerned with identifying processes of injustice that can be resolved than with devising a perfectly just society. It follows that she does not have a clear and systematized concept of what she understands for justice. For her we must consider that a situation is unfair when social groups, in detriment of the structural position they occupy, suffer domination or oppression. As a result, injustice to Young is structural. Democracy is placed by the philosopher as the central way to promote justice, which when does not work well can contribute to injustice by keeping certain groups excluded. For this reason, Young reviews the conception of deliberative democracy to make it more inclusive of marginalized social groups. She proposes to broaden the mechanisms of communication, review the notion of representation and reflect on governance exercised at the local and global levels. In this discussion, Young suggests that we should push democracy across borders. Finally, to consider how unintended individual actions link to unfair structural social processes, Young consider the level of structural action of individuals rather than the interactional level. At the structural level people contribute to unfair processes through everyday habits and practices, so their actions and choices must be subject to some kind of judgment - political responsibility. For this reason, Young was concerned with defining the kind of responsibility we should give individuals for injustice, as their actions are being disregarded by theories of justice, although they are fundamental to making the world less unfair.